(untitled) (Journal of Nematode Morphology and Systematics, 2012)
The present paper deals with the description/record of 18 species, four new and 14 known, representing the Order Mononchida from Japan. Clarkus enigmatus sp. n. has body 1.54-2.07 mm long, lip region wide and offset, buccal cavity slightly asymmetrical and 32-36 x 17-19 μm, large dorsal tooth with its apex at 84-87% of stoma length from base, subventral ridge slightly dentate at its proximal end, female genital system amphidelphic, echinulate eggs, and tail conical elongate and curved ventrad. Prionchulus japonicus sp. n. has body 1.58-1.84 mm long, lip region offset and wider than the adjoining body, buccal cavity 34-36 x 19-20 μm, dorsal tooth apex at 80-83% from base of buccal cavity, subventral ridges with 10-13 moderately developed denticles, amphids at level of the anterior end of the buccal cavity, pars refringens vaginae with three drop-shaped sclerotized pieces, uterine egg 117 x 74 μm, tail 104-128 μm long and curved ventrad with a dorsal depression near the terminus and sharply pointed tip. Mylonchulus monhystera sp. n. has body 1.08-1.14 mm long, lip region offset and distinctly wider than the adjoining body, buccal cavity 25- 28 x 15-16 μm, dorsal tooth large and claw-like with its apex at 80-84% from base of buccal cavity, subventral teeth well developed, ventrosublateral denticles arranged in 5 or 6 rows, female genital system mono-prodelphic with very small post-uterine sac, V = 70-75, tail 25-35 μm long, curved ventrad, and often with sudden narrowing near terminus giving a digitate appearance, and caudal glands well developed with terminal spinneret. Miconchus nipponi sp. n. has body 1.87-2.21 mm long, lip region offset by depression, amphid aperture at level with the middle of the praeparietale of buccal cavity, dorsal and subventral teeth similar in shape and size and located at 30-33% from base of stoma, female genital system amphidelphic, three well developed, blister-like vulval papillae present anterior and occasionally also posterior to vulva, spicules slightly curved ventrad and about 1.5 times the body diameter long, gubernaculum with its distal end appearing as two dorsally bent finger-like projections, lateral guiding pieces with bifid distal end, 11 well developed, regularly spaced ventromedian supplements, tail curved ventrad and gradually narrowing to a truncate extremity, and caudal glands grouped and with terminal spinneret. Mononchus truncatus, Clarkus papillatus, C. sheri, Prionchulus muscorum, P. punctatus, Coomansus parvus and Iotonchus parabasidontus are recorded for the first time from Japan. Additional morphometric data are also provided for Actus salvadoricus, Mylonchulus brachyurus, M. sigmaturus, M. oceanicus, Iotonchus arcuatus and Miconchus japonicus. And one specimen of an unknown species of Miconchus has also been described.